(untitled) (African Journal of Biomedical Research, 2023)
Maternal mortality remains remarkably high in low and middle-income countries, accounting for 94% of maternal death with Midwives serving as the main providers of skilled care to curb the menace. Little attention is paid to their experiences of stress and burnout in Calabar Cross River State, Nigeria. The study utilized a descriptive Cross-Sectional design and total population sampling technique to recruit 255 midwives from two selected hospitals. A validated Expanded Nursing Stress Scale (ENSS) with a reliability coefficient of 0.7 was used for data collection. Data was analyzed using SPSS 21.0 software and chi-square used for inferential statistics. The total mean stress scores for all sub-scale was generally high ranging from 7.76 in 3 items related to inadequate preparation sub-scale to 9 items related to workload with a mean of 27. 68 (SD: 7.29; Min: 9.0; Max 70.0). The high total means indicate frequently and extremely stressful level of stress. Moreover, the majority 208(81.6%) participants experienced stress in midwifery related services. 63 (25.0%) experienced burnouts. No significant relationship (P = <0.05) existed between year of working experience and experience of stress among midwives. Recognizing and managing stress is imperative in the health care system as midwives in Nigeria are tasked with the responsibility of reducing maternal morbidity and mortality. Solutions to these challenges include increasing the numbers of midwives and improving clinical environment of midwives to improve quality of care and aid the attainment of sustainable development goals three and four in Nigeria.